The Effect of Toxic Friendship on Students' Mental Health - Esperansa, Serafina Trixi; Siva, Nur; Putri Saraswati , Ida Ayu; Wisnawa, Kadek Sukma Cahyani; Kistian, Agus (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2023)
This study aims to investigate the influence of toxic friendships on students' mental well-being. Specifically, it examines the detrimental effects of negative relationships within friendships on individuals' mental states. The research focuses on students enrolled in the Communication Science Study Program at Mercu Buana University Yogyakarta, Class of 2021. A sample of 135 students was selected using a simple random sampling technique from a population of 226. This type of research is quantitative research with a survey method approach. This study employing a modified questionnaire titled "Effect of Toxic Friendship on Student Mental Health" as the primary data collection instrument. The data obtained is then analyzed using SPSS software. The results indicated that toxic friendship has no effect on students' mental health. The instrument in this study used a questionnaire. The results showed that toxic friendship has no effect on students' mental health. The study underscores the need for further research to better understand the complexities of social relationships and their implications for mental health. This work contributes to the ongoing discourse on the factors affecting students' psychological well-being in educational settings.